Evaluation of Capability Improvement of Government Internal Control Apparatus - Yusup, Muhammad; Rahadian, Yan (Universitas Muhammadiyah Surakarta, 2023)
Evaluation of the improvement of the capability of the Government Internal Supervisory Apparatus (APIP) is very important considering that APIP capability has a significant impact on strengthening the effectiveness of the Government Internal Control System (SPIP) to realize good governance. The Sukabumi District Inspectorate was chosen as the object of research because it is one of 362 APIPs with a level below Level 3 from the results of the BPKP assessment in 2021. After using the new regulation, the APIP capability of Sukabumi District Inspectorate is at Level 3. This research used qualitative method with evaluation case study type. The evaluation framework refers to the new and old regulations related to APIP capability assessment. Based on the results of the comparative analysis of old and new regulations, it can be concluded that the new regulations on improving APIP capability are clearer and more systematic than the old regulations. From the evaluation results based on the new regulations APIP has not been able to reach level 3 as a result of its self-assessment. There are 3 topics that are not yet appropriate, namely supervisory planning, performance audits and compliance audits.